(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): We will research which of the factors, vision, inspiration and integrity contribute most to the success of organizational management. Purpose: The purpose and goal of the research is to check what the vision, inspiration and integrity means at all, and to determine which of the factors considered most helpful in managing organizations. Method: The study will use a descriptive method. We will collect literature, articles and information and review and analyze them. Results: Research has shown that the successful management organizations need to consider all three factors considered, vision, inspiration and integrity. Organization: The organization will be able to analyze the survey and find out with the leaders how the management would be more suitable for even more successful business operations. Society: The organization may invest in the development of individual leadership skills, and encourages them to develop their talents, potentials and qualities Originality: The study included three factors that contribute to better management organizations. Limitations/Future Research: Research has been done on the basis of the collected literature, articles and information.